A Plastic Scintillator Based on an Efficient Thermally Activated Delayed Fluorescence Emitter 9‐(4‐(4, 6‐diphenyl‐1, 3, 5‐triazin‐2‐yl)‐2‐methylphenyl)‐3, 6‐dioctyl‐9H‐carbazole for Pulse Shape Discrimination Measurement. Issue 7 (25th January 2021) - Chen, Tianheng; Yu, Hao; Wen, Xianfei; Redding, Caleb; Hajagos, Tibor Jacob; Zhao, Hongxiang; Hayward, Jason P.; Yang, Chuluo; Pei, Qibing
Abstract: Pulse shape discrimination (PSD)‐capable plastic scintillator is in demand for the detection of high‐energy neutrons in the presence of gamma radiation background. Conventional PSD plastics are based on delayed fluorescent dye via triplet–triplet annihilation of a fluorescent dye additive, which is inefficient to harvest the energy of triplet excitons. In recent years, thermally activated delayed fluorescence (TADF) emitters have gained substantial success in organic light‐emitting diodes due to their efficient utilization of the energy of triplet excitons and thereby achieving theoretical unity internal quantum efficiencies. Herein, a highly efficient TADF dye 9‐(4‐(4, 6‐diphenyl‐1, 3, 5‐triazin‐2‐yl)‐2‐methylphenyl)‐3, 6‐dioctyl‐9 H ‐carbazole is reported for the PSD application. This TADF dye may be loaded up to 30 wt% in polyvinyltoluene matrix and still retains high optical transparency. High scintillation light yield and PSD figures of merit are obtained from the TADF plastic. With the introduction of a secondary dye to further increase the utilization efficiency of the excitation energy, the light yield is increased to 6948 photons MeV −1 . The measured alpha/gamma PSD figure of merit is 1.12 at the energy threshold of 100 keVee and neutron/gamma PSD figure of merit is 1.32 at the threshold of 1000 keVee. Abstract : A new thermally activated delayed fluorescence emitter 9‐(4‐(4, 6‐diphenyl‐1, 3, 5‐triazin‐2‐yl)‐2‐methylphenyl)‐3, 6‐dioctyl‐9 H ‐carbazole is developed by integrating modified carbazole donor with cyaphenine for organic plastic scintillators, and the plastic scintillator fabricated with this emitter with a proper wavelength shifter demonstrates a high light yield of ≈7000 photons MeV –1 and a neutron/gamma pulse shape discrimination figure of merit of 1.32 at the energy threshold of 1000 keVee.